2018
DOI: 10.1007/s00277-018-3332-7
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive CD8+ T cell and MHC class I signatures in polycythemia vera patients

Abstract: Polycythemia vera (PV) is a myeloproliferative neoplasm characterized by overproduction of red blood cells. We have performed a comprehensive characterization of blood immune cells for expression of naïve and memory receptors as well as βm-associated and βm-free MHC class I heavy chains, also known as closed and open conformers, respectively, in PV patients and age-matched controls (CTR). We show that the peripheral CD3CD8 T cell pool in PV patients is clearly divided into two discrete populations, a more gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…In addition, patients with PV have increased levels of terminally differentiated CD8+ T cells and lower levels of naïve T-cells compared to healthy age-matched controls. They also display lower levels of stable cell surface human leukocyte antigen (HLA)-I [64].…”
Section: Immune-subversive Mechanisms In Mpnmentioning
confidence: 99%
“…In addition, patients with PV have increased levels of terminally differentiated CD8+ T cells and lower levels of naïve T-cells compared to healthy age-matched controls. They also display lower levels of stable cell surface human leukocyte antigen (HLA)-I [64].…”
Section: Immune-subversive Mechanisms In Mpnmentioning
confidence: 99%
“…Recent data provide evidence for coreactive CD8+ T-cells in hematologic diseases such as polycythemia vera [16], but with an immunophenotype different from the aberrant T-cell population described here.…”
Section: Discussionmentioning
confidence: 52%
“…In the current study, we found that T-cell subsets of patients with MF shifted from a quiescent to an activated state and that treatment with ruxolitinib reduced the activation of both helper CD4 and cytotoxic CD8 T cells in a time-dependent manner (Figure 8). The activation pattern of CD8 + T cells was significantly similar to that of polycythemia vera, 31 including decreased TN and TCM, unaltered TEM and increased TEFF subsets. However, in MF, CD4 + cells were also considerably skewed toward an effector cell phenotype, unlike polycythemia vera.…”
Section: Discussionmentioning
confidence: 60%